2012
DOI: 10.1111/j.1467-8489.2012.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing economic performance of organic and conventional U.S. beef farms using matching samples*

Abstract: Economic performance measures of organic and transitioning-to-organic cow-calf farms are compared with those of non-organic cow-calf farms. A method of matching samples is used for the comparison, estimating sample average treatment effects for the subpopulation of the treated. Each organic farm is matched with one non-organic farm that is involved in the same beef industry segments and farm size classes, and in the same region. Furthermore, farmer demographic, farming system, and technology variables are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…The organic beef industry is in the early stages of development in the United States; however, markets for organic meat have expanded rapidly over the past decade as consumers consider potential human health and environmental benefits (Dimitri and Oberholtzer, 2009). As consumers are demanding natural, local, organic, and grass-fed animal products, an opportunity exists for organic dairy producers to capitalize on the growing organic beef industry (Gillespie and Nehring, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The organic beef industry is in the early stages of development in the United States; however, markets for organic meat have expanded rapidly over the past decade as consumers consider potential human health and environmental benefits (Dimitri and Oberholtzer, 2009). As consumers are demanding natural, local, organic, and grass-fed animal products, an opportunity exists for organic dairy producers to capitalize on the growing organic beef industry (Gillespie and Nehring, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An exact match was based on the dairy farm herd size within the 8 states specified earlier. Following Gillespie and Nehring (2012), dairy cows were grouped into 7 herd-size categories: (1) <50 cows, (2) 50 ≤ cows <100, (3) 100 ≤ cows <200, (4) 200 ≤ cows <500, (5) 500 ≤ cows <1,000, (6) 1,000 ≤ cows <2,000, and (7) >2,000 cows. This herd-size classification allowed us to capture the size distribution common to the different regions, with smaller herds typically located in the Midwest and East and larger herds representative of states in the West.…”
Section: Matching Variablesmentioning
confidence: 99%
“…Matching methodology has been applied to the dairy industry to demonstrate that using recombinant bovine somatotropin (rbST) resulted in increased production per dairy cow, decreased cost of production per hundredweight of milk produced, and increased labor and management income per operator on dairy farms in New York State (Tauer, 2009). Organic production was studied using matching methods and it was found that organic cow-calf operations experienced higher allocated costs compared with conventional operations (Gillespie and Nehring, 2012) and that organic crop producers did not realize increased incomes compared with conventional crop producers (Uematsu and Mishra, 2012). Mayen et al (2012) found that organic technology was less productive than conventional farm technology when matching on-farm and operator characteristics using technical efficiency measures.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to organic beef cattle farms, although there is controversy, studies mainly show that organic farms have worse economic results than their conventional counterpart when they are studied by farm and year since they used to have longer production cycles when the farms are under the Common Agricultural Policy's (CAP) conditions [25,59,129] or not [74]. They are also more dependent on both subsidies and premium prices.…”
Section: Implementation Of Organic Farms: Its Consequences On the Farmentioning
confidence: 99%
“…They are also more dependent on both subsidies and premium prices. Finally, higher production costs (mainly derived from feeding and during the conversion period) have also been observed [25,59,[74][75]129].…”
Section: Implementation Of Organic Farms: Its Consequences On the Farmentioning
confidence: 99%